Hemodynamic responses of resistance exercise performed with repetitions to failure and not to failure in adults with hypertension. Issue 1 (February 2021) - Domingues, Lucas B.; Cadore, Eduardo L.; Ferrari, Rodrigo
Abstract : Objective: To evaluate and compare the hemodynamic responses of resistance exercise (RE) performed with repetitions to failure vs. not to failure in individuals with hypertension. Methods: Twenty participants were randomly allocated to perform three experimental sessions: a RE session performed with repetitions to failure (RF); a RE session performed with repetitions not to failure (NRF); and a non-exercise control session (Con). RE sessions were composed of four sets of 10 repetitions in four exercises involving large muscle groups. To ensure that the sets could be performed with RF or NRF, intensities corresponding to 75% and 50% of one-repetition maximum test were adopted in RF and NRF sessions, respectively. The Con was performed in seated rest. Blood pressure and rate-pressure product were measured before, during and after the experimental sessions for 1 h. Results: SBP and DBP decreased after NRF compared with Con (systolic post 1 h: –7.7 ± 1.1 mmHg, P < 0.001; diastolic post 1 h: –4.2 ± 0.7 mmHg, P = 0.001), and after RF compared with Con (systolic post 1 h: –8.2 ± 1.3 mmHg, P < 0.001; diastolic post 1 h: –7.4 ± 1.4 mmHg, P < 0.001). No significant difference was found in blood pressure between RF and NRF sessions after 1 h. Rate-pressure product was lower during NRF compared with RF ( P = 0.001), suggesting a higher cardiovascular demand during the RF session. Conclusion: The RF and NRF sessions are equally effective to promote post-exercise hypotension. In addition, NRF session can reduce cardiac demand during the exercise and should be recommended in adults with hypertension.